Community engagement for healthcare delivery without incentive: sustainable or not for Universal Health Coverage? - Pandey, Archana; Kumar, Alok; Agarwal, Neeraj; Bharti, Anju; Kumar, Neeta; Kansal, Sangeeta (Indian Journal of Community Health, 2025)
Apart from healthcare service delivery, the growing digitalization of health records raises a need to connect every citizen with a digital health ecosystem under the Ayushman Bharat Digital Mission. Considering this fact, an ICMR-funded project, the human resource in the form of Home Health Guides (HHGs) is envisaged to bridge the gap between the community and the health system as complementary to the existing health workforce. These are active volunteers in the community who are educated till matriculation and are willing to work in the field for at least two or three hours without any incentives/remunerations. Their assigned roles are to record and update the health-related information of the assigned families. They are also supposed to assess health emergencies, guide the community regarding their healthcare needs, and link them with the existing healthcare system. As part of the project, we have provided hand-holding support, training, and a few other non-monetary incentives in the form of first aid and medical tool kit, stationary, etc. It was observed that along with the health system, the community also needs the assistance of such a cadre for updating their health records. Also, despite so much effort, these volunteers are not motivated therefore, such initiatives need to be revised and should include monetary incentives to keep them motivated.